O processo de construção da Unesp Corporativa - Bizelli, Jose Luis [UNESP]; Cunha, Maira Darido da [UNESP] (My University, 2013)
The article presents São Paulo State University Corporate Education Program – UNESPCorp – whose target is to evolve the staff of institution in order of their professional improvement, using distance education technologies (D-learning). The UNESPCorp pilot project started with the Improvement in Bidding and Public Employment curse. The curse was taught on the second semester of 2012 and received 130 employees representing all UNESP campuses. The text was divided in two parts, the first part recovers historical context which introduces the Corporate University. The second part presents challenges and advances represented for the first version of course, even as its pedagogical structure of operation.

O artigo apresenta o Programa de Educação Corporativa da Universidade Estadual Paulista – UNESPCorp –, cujo objetivo é desenvolver o quadro de pessoal da instituição rumo ao seu aprimoramento profissional, utilizando tecnologias de educação à distância (EaD). O projeto piloto da UNESPCorp foi iniciado com o curso de Aperfeiçoamento em Licitação e Contratação Pública. O curso foi realizado no segundo semestre de 2012 e recebeu 130 servidores representando todos os campi da UNESP. O texto está dividido em duas partes, sendo que a primeira recupera o contexto histórico no qual se insere a Universidade Corporativa. A segunda parte apresenta os desafios e avanços representados pela primeira versão do curso, assim como sua estrutura pedagógica de funcionamento.
The process of construction of São Paulo State University corporate education program – UNESPcorp
Keywords: Distance education; Corporate university; Continuing education for work; Educação; Educação a distancia; Educação corporativa